Ultrasmall Superparamagnetic Iron Oxide Imaging Identifies Tissue and Nerve Inflammation in Pain Conditions. Issue 4 (21st November 2017) - Shen, Shiqian; Ding, Weihua; Ahmed, Shihab; Hu, Ranliang; Opalacz, Arissa; Roth, Sarah; You, Zerong; Wotjkiewicz, Gregory R; Lim, Grewo; Chen, Lucy; Mao, Jianren; Chen, John W; et al.
Abstract: Objective: Correlation between radiologic structural abnormalities and clinical symptoms in low back pain patients is poor. There is an unmet clinical need to image inflammation in pain conditions to aid diagnosis and guide treatment. Ferumoxytol, an ultrasmall superparamagnetic iron oxide (USPIO) nanoparticle, is clinically used to treat iron deficiency anemia and showed promise in imaging tissue inflammation in human. We explored whether ferumoxytol can be used to identify tissue and nerve inflammation in pain conditions in animals and humans. Methods: Complete Freud's adjuvant (CFA) or saline was injected into mice hind paws to establish an inflammatory pain model. Ferumoxytol (20 mg/kg) was injected intravenously. Magnetic resonance imaging (MRI) was performed prior to injection and 72 hours postinjection. The changes in the transverse relaxation time (T2) before and after ferumoxytol injection were compared between mice that received CFA vs saline injection. In the human study, we administered ferumoxytol (4 mg/kg) to a human subject with clinical symptoms of lumbar radiculopathy and compared the patient with a healthy subject. Results: Mice that received CFA exhibited tissue inflammation and pain behaviors. The changes in T2 before and after ferumoxytol injection were significantly higher in mice that received CFA vs saline (20.8 ± 3.6 vs 2.2 ± 2.5, P = 0.005). In the human study, ferumoxytol-enhanced MRI identified the nerve root corresponding to the patient's symptoms, but the nerve root was not impinged by structural abnormalities, suggesting the potential superiority of this approach over conventional structural imaging techniques. Conclusions: Ferumoxytol-enhanced MRI can identify tissue and nerve inflammation and may provide a promising diagnostic tool in assessing pain conditions in humans.